Cross-dressing in the Declamations of Choricius of Gaza - Hadjittofi, Fotini (2016)
Cross-dressing is a major theme in two of Choricius’ declamations: the Lydians (Declamation 3) and the War-Hero (Declamation 11). In both declamations dress is considered, by the speakers themselves, a significant marker of gender identity, so that putting on feminine clothes seriously jeopardises the cross-dresser’s masculine status – a line of reasoning that sees gender as socially constructed. The opposite argument, however, is latent in both speeches. This paper argues that Choricius (and in this he is not alone among Greek Late Antique orators) promulgates an essentialist view of gender, which dismisses dress and physical appearance as reliable indicators for the condition of the inner self. While for many Christian thinkers the condition (or appearance) of the body reveals and/or influences the condition of the soul, there are “essentialist” trends not only in their own thinking, but also (and more strikingly) in popular stories about saints and martyrs, some of which even involve transvestism. It is also relevant for the dissociation between the (effeminate) appearance and the (masculine) reality of Choricius’ transvestites that there emerges in Late Antiquity a sense of privacy, which allows an individual to lead an entirely secret life, which could contrast with his/her public image.